Rekonstruksi Tindakan Afirmatif Bantuan Hukum Penyandang Disabilitas Perspektif Tujuan Hukum Guctav Radbruch - Musdin, Rasyid (SIYASI: Jurnal Trias Politica, 2023)
Law No. 16/2011 on Legal Aid needs to be reconstructed because there are inequalities related to the provision of legal aid to persons with disabilities. The Legal Aid Law states that all provisions for the provision of legal aid are subject to the Legal Aid Law which is substantively unfriendly to persons with disabilities as individuals who need special treatment based on equal rights. This research is a normative legal research using a statutory approach, theoretical approach and analytical approach. The analysis is conducted by analysing Law No.16/2011 on Legal Aid for persons with disabilities and Gustav Radbruch concept of legal objectives. By elaborating the thought of Gustav Radbruch legal objectives, there are two discussion formulations. First, how Gustav Radbruch legal objectives view the Legal Aid Law for persons with disabilities. Second, the legal reconstruction of affirmative action for legal aid for persons with disabilities from the perspective of Gustav Radbruch legal objectives. The results of the discussion show that the Legal Aid Law does not provide justice value, benefit value and certainty value for persons with disabilities, so it is necessary to reconstruct the law of affirmative action for persons with disabilities in the Legal Aid Law in order to guarantee the fulfilment of the right to legal aid for persons with disabilities.